MRSA: A Challenge to Norwegian Nursing Home Personnel - Thorstad, M.; Sie, I.; Andersen, B. M. (Interdisciplinary Perspectives on Infectious Diseases, 2011)
In Norway, methicillin-resistant Staphylococcus aureus (MRSA) is increasing in primary healthcare, associated with imported cases and outbreaks in long-term care. According to Norwegian national guidelines, MRSA-exposed healthcare workers (HCWs) and patients are tested. Carriage of MRSA leads to exclusion from work in healthcare institutions. In this study, 388 staff members in 42 nursing homes in Oslo County responded to questions about personal experience with MRSA and of own attitudes to challenges associated with the control and treatment of MRSA patients. Half (52%) of the nursing staff were concerned of becoming infected with MRSA and the consequences of this would be for own social life, family, economy, and work restriction. The concern was associated with risk factors like old buildings not suitable for modern infection control work, low staffing rate (70% without specific training in healthcare and 32% without formal healthcare education), defective cleaning and decolonization, and lack of formal routines and capacity for isolation of MRSA patients. Since the Norwegian MRSA guideline permits patients with persistent MRSA infections to move freely around in nursing homes, the anxiety of the staff to become infected and excluded from job was real.